Cell Based Treatment for Spinocerebellar Ataxia: A Clinical Case Report - Damar Dyah Mentari; Rivan Danuaji (Magna Neurologica, 2026)
Background: Spinocerebellar ataxia (SCA) is a dominant and monogenic central nervous system disorder, characterized by progressive motor disorders affecting coordination, balance, speech, and ADL. The prevalence is 2.7 out of 100,000 people. Currently, cell-based therapy is being developed for clinical improvement in SCA. Case: A 48-year-old woman with weakness in both legs and arms, difficulty walking, dysmetria, and dysarthria since 2015. Examination of SARA scoring is severe ataxia, EMG showed polyradiculopathy, muscle denervation, and suspicion of posterior ramus lesions; complete blood laboratory and tumor markers were routine. MRI brain contrast and whole spine contrast radiology imaging were also performed. Clinical improvement was achieved in 2016 following stem cell injection in Thailand (dose and type of cells unknown). However, clinical worsening occurred from 2020 to 2024. The patient received Umbilical Cord Mesenchymal Stem Cells (MSC) in October 2024, administered intrathecally at a dose of 20 million cells. Discussion: The first injection showed significant clinical improvement. The second injection showed no clinical improvement, but no worsening of symptoms was found. The difference in results may be due to variations in the route of administration, cell type, cell quality, and the dose administered. Conclusion: The administration of umbilical cord mesenchymal stem cells (UC-MSCs) in SCA is considered safe, with minimal complications, and can suppress disease progression, although it does not produce clinical improvement.